2013
DOI: 10.1002/anie.201309160
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a Complex Formed by a Protein and a Helical Aromatic Oligoamide Foldamer at 2.1 Å Resolution

Abstract: In the search of molecules that could recognize sizeable areas of protein surfaces, a series of ten helical aromatic oligoamide foldamers was synthesized on solid phase. The foldamers comprise three to five monomers carrying various proteinogenic side chains, and exist as racemic mixtures of interconverting right-handed and left-handed helices. Functionalization of the foldamers by a nanomolar ligand of human carbonic anhydrase II (HCA) ensured that they would be held in close proximity to the protein surface.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 70 publications
0
37
0
1
Order By: Relevance
“…Moreover, other very recent, intriguing results will greatly stimulate additional research in the fundamental field (chiral helix···helix interactions) of biomolecular processes. They include (i) stereoselectivity of the self‐assembly of left‐handed and right‐handed peptide screws with generation of novel collagen triple helix mimetics, using (Pro‐Pro‐Gly) 10 enantiomeric sequences as minimal building blocks ; (ii) polymorphism complexity (twist, chirality, and handedness inversion) exhibited by self‐aggregated peptides resulting in amyloid fibrils ; and (iii) preferred handedness of helical foldamers induced upon interaction with a protein surface .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, other very recent, intriguing results will greatly stimulate additional research in the fundamental field (chiral helix···helix interactions) of biomolecular processes. They include (i) stereoselectivity of the self‐assembly of left‐handed and right‐handed peptide screws with generation of novel collagen triple helix mimetics, using (Pro‐Pro‐Gly) 10 enantiomeric sequences as minimal building blocks ; (ii) polymorphism complexity (twist, chirality, and handedness inversion) exhibited by self‐aggregated peptides resulting in amyloid fibrils ; and (iii) preferred handedness of helical foldamers induced upon interaction with a protein surface .…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] The topic is particularly attractive in view of 1) the wide variety of ligands provided by supramolecular chemistry,a nd 2) the continuing challengeo ftargeting protein surfaces, with their unique patchworks of hydrophobic, polar and charged regions. Efforts to approximate protein surfaces with supramolecular ligands have involved calixarenes, [1,[5][6][7][8][9][10][11][12] crown ethers, [13][14][15] curcurbiturils, [16][17][18][19] foldamers, [20][21][22][23] porphyrins [24][25][26][27][28][29][30][31] andt weezers. [2,[31][32][33] Recent attention has focusedo n the cationic side chains of lysine and arginine as potentialt argets that protrudei nvitinglyf rom the protein surface.…”
Section: Introductionmentioning
confidence: 99%
“…When equilibrium deviates from a 50:50 mixture, CD bands emerge. This technique has recently been used to screen short quinoline oligoamide sequences tethered to human carbonic anhydrase II (HCA) through a ligand (Figure 2), and a sequence was identified that not only possessed affinity for the protein surface but also induced the formation of a new HCA dimer 5. The induction of helix handedness has also been observed between a fully cationic side‐chain‐functionalized tetramer and G‐quadruplex DNA6 and between helical capsules and their chiral guests 7.…”
Section: Introductionmentioning
confidence: 99%